Implications of Student's Online Learning Experience on Social and Emotional Behavior - Qoerul Ahmad Tabiin; Soimatul Khomisah; Agus Sutiyono; Shodiq Abdullah (Social Sciences and Education Research Review)
This study aims to explore the implications of students' online learning experiences on social and emotional behavior in Akidah Akhlak subjects at Madrasah Tsanawiyah Hidayatullah Temanggung Indonesia during the Covid-19 pandemic. This study uses a qualitative descriptive design with the type of field research. Data were obtained from students who took part in Akidah Akhlak learning. The method used is interviews, observation and documentation, then reduced, presented and analyzed. The results of this study indicate that online learning has an impact on social and emotional behavior including students being less cooperative because they rarely play together, lack tolerance, lack of socializing with friends, limited learning at home, children's emotions sometimes feel bored and sad.